A Prussian blue analogue as a long-life cathode for liquid-state and solid-state sodium-ion batteries. Issue 20 (15th September 2020) - Huang, Tianbei; Du, Guangyuan; Qi, Yuruo; Li, Jie; Zhong, Wei; Yang, Qiuju; Zhang, Xuan; Xu, Maowen
Abstract : A facile wet-chemical method for synthesizing a nano-sized NiFe-PBA compound with excellent electrochemical performance. Abstract : Prussian blue analogues (PBAs) as a kind of promising cathode material for sodium-ion batteries (SIBs) have attracted much attention due to their low price and open three-dimensional (3D) channel structure. Here, a facile wet-chemical method is used to synthesize a nano-sized NiFe-PBA compound. The as-synthesized NiFe-PBA not only exhibits good structural stability but also demonstrates impressive electrochemical performance when it is used as a cathode in SIBs. Both liquid-state and solid-state sodium-ion batteries (SSIBs) demonstrate excellent cycling stability with a capacity retention of 85.8% and 86.7%, respectively, after 1120 cycles.